2014
DOI: 10.1155/2014/589345
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Resolution for Product Performance Requirements Based on Propagation Analysis in the Extension Theory

Abstract: Traditional product data mining methods are mainly focused on the static data. Performance requirements are generally met as possible by finding some cases and changing their structures. However, when one is satisfied with the structures changed, the other effects are not taken into account by analyzing the correlations; that is, design conflicts are not identified and resolved. An approach to resolving the conflict problems is proposed based on propagation analysis in Extension Theory. Firstly, the extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In low-carbon design, since E and C are both single factors in each stage, and P is integrated by multiple factors in each of eight stages of product life cycle, 42 in this section we mainly study attribute transformation of performance P. Suppose the j 3 th performance attribute of a product case P ij 1 j 2 j 3 on the third layer of the ith stage can be transformed. It includes three scenarios: (1) deletion transformation of P ij1j2j3 , (2) increase transformation of P ij 1 j 2 j 3 , and (3) substitution transformation of P ij 1 j 2 j 3 :…”
Section: Dynamic Classification Based On Attribute Transformationmentioning
confidence: 99%
“…In low-carbon design, since E and C are both single factors in each stage, and P is integrated by multiple factors in each of eight stages of product life cycle, 42 in this section we mainly study attribute transformation of performance P. Suppose the j 3 th performance attribute of a product case P ij 1 j 2 j 3 on the third layer of the ith stage can be transformed. It includes three scenarios: (1) deletion transformation of P ij1j2j3 , (2) increase transformation of P ij 1 j 2 j 3 , and (3) substitution transformation of P ij 1 j 2 j 3 :…”
Section: Dynamic Classification Based On Attribute Transformationmentioning
confidence: 99%
“…And the design objective is typically based on designer experience, and the value of the design objective cannot be determined effectively. Zhao et al (2015) extracted design objectives from technical criteria and cost, which can be used to obtain the reliable principle solution. Tao et al (2015) identified the product function objective based on user preferences and requirements and created a conceptual scheme that satisfied user requirements.…”
Section: Introductionmentioning
confidence: 99%
“…34 In Extenics, 35 it adopts the basic-element theory, including matter-element, affair-element, and relation-element, to represent the conflict problem in a formalized model; uses the dependent function to quantitatively identify and evaluate the conflict problem; and employs detailed transformation operations to transform the generic strategies into the feasible design scheme. Zhao et al 36 propose the conflict solution for product performance requirements based on propagation analysis in Extenics; improve the retrieval method to get similar cases, implement transformation operations on the similar cases by propagation analysis, and evaluate the effect and level of propagation to achieve the optimal scheme. Tang et al 37 integrate extension transformations and gene expression programming (GEP) for incompatible problems and overcome the combination explosion of schemes.…”
Section: Introductionmentioning
confidence: 99%